EMPOWERING STUDENTS’ READING COMPREHENSION ON EXPLANATION TEXT THROUGH GIST STRATEGY - Chamidah, Ayu Indah Nur (RETAIN, 2021)
The purposes of this research are to know the improvement of students’ scores in comprehending explanation text after using GIST (Generating Interactions between Schemata and Text) strategy, to explain the implementation of GIST strategy, and to reveal students’ responses towards the implementation of GIST strategy for teaching explanation text. This study used quantitative method to know the improvement of students’ scores. Besides, this study also used qualitative method to explain the implementation of GIST strategy and students’ responses. There were 22 students of XI IPA 1 who participated in this study. The researcher used test, observation, and interview to collect the data. The data were analyzed by using SPSS to know the improvement of students’ scores The result of this research showed that there was a significant improvement from the implementation of GIST strategy to the students’ reading comprehension. It could be seen from the value of the t-test that the students’ scores was higher than the t-table (5.524>2.074). Additionally, the mean score of pre-test which was 72.27 had improved to 89.77 in post-test. The use of GIST strategy made the students easier to understand the main idea of the explanation text. Therefore, it can be stated that GIST strategy gives significant improvement of students’ reading comprehension in understanding explanation text. Keywords: Reading, Reading Comprehension, GIST Strategy, Explanation Text